Development of Muay Thai Teaching Model - Leepromma, Samarnchai (Academic Journal of Thailand National Sports University, 2016)
The purpose of this research was to develop teaching Muay Thai model for preservation in Muay Thai course 1 for the first year students. The samples used in this research were 25 Muay Thai teachers teaching sport School, 40 Muay Thai instructors in physical Education Institute, 100 teachers teaching Muay Thai in the Provincial Arts of Muay Thai Preservation Center under Arts of Muay Thai Preservation Institute, Department of Physical Education, the Ministry of Tourism and Sports, 2 instructors teaching Muay Thai at the College of Muay ai Education and Rajabhat University and 40 students at Physical Education Institute, Maha Sarakam campus. The samples were purposive and simple random sampling. The instrument used in this research was consisted of Muay Thai Teaching document for preservation, lesson plans, interview form, evaluation forms on Muay Thai Teaching Model for Preservation, learning behaviors, preservation behaviors, Muay Thai skills for preservation, knowledge and understanding assessment form and attitude measurement towards the usage of Muay Thai teaching model for preservation. The statistics for data analysis were percentage, mean, standard deviation and t-test. The research findings were as follows: The comparative achievement for both pretest and posttest of using the Muay Thai teaching model for preservation revealed the posttest was significantly higher than the pretest at .01 level. There were 80 students having positive learning behaviors and passing the evaluation criteria individually 80%. The students' behaviors on the arts of Muay Thai preservation were overall in high level (90.18%) higher than the required criteria (80%) The students' Muay Thai skills on preservation were overall in high level (89.77%) and passing the required evaluation criteria individually (80). The students' attitudes towards learning organization according to Muay Thai teaching model for preservation were overall and individually in high level.